2021
DOI: 10.1182/blood.2019003977
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and antiplatelet treatments in cancer

Abstract: Platelets have been hypothesized to promote certain neoplastic malignancies, however, antiplatelet drugs are still not part of routine pharmacological cancer prevention and treatment protocols. Paracrine interactions between platelets and cancer cells have been implicated in potentiating the dissemination, survival within the circulation, and extravasation of cancer cells at distant sites of metastasis. Signals from platelets have also been suggested to confer epigenetic alterations including upregulating onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 140 publications
(98 reference statements)
0
47
1
1
Order By: Relevance
“…This study also reported that the use of antiplatelet therapy tended to delay the deterioration of liver function in these patients (269). Recent summaries of outcomes data in cancer prevention have also highlighted the cancer mitigating role of aspirin and other agents (270).…”
Section: Platelet Activation and Aggregationmentioning
confidence: 60%
“…This study also reported that the use of antiplatelet therapy tended to delay the deterioration of liver function in these patients (269). Recent summaries of outcomes data in cancer prevention have also highlighted the cancer mitigating role of aspirin and other agents (270).…”
Section: Platelet Activation and Aggregationmentioning
confidence: 60%
“…To further study the mechanism of THCMA inhibiting arterial thrombosis and tumor growth, 2 the antiplatelet activity of THCMA was evaluated in two ways: AFM of platelets in the presence and absence of THCMA and in vitro platelet-aggregation assay. Figure 9A shows resting rat platelets on AFM.…”
Section: Resultsmentioning
confidence: 99%
“… 1 Its overexpression occurs not only on the vascular endothelium of tumors but also on lung, ovarian, lymphoma, and breast cancer cells. 2 As an adhesion molecule, P-selectin binds with P-selectin glycoprotein ligand 1 (PSGL1), the cognate ligand expressed on leukocytes, T cells, and myeloid, lymphoid, carcinoma, and dendritic cells. 3 , 4 This binding mediates the adhesion of platelets, leukocytes, T cells, endothelial cells, and tumor cells, resulting in inflammation, thrombosis and tumor growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets have an important role in cancer development, progression, and metastasis ( 117 , 119 , 130 , 131 ). Thrombocytosis has been associated with worse outcomes in several types of cancer, including lung, colorectal, ovarian, and hepatocellular carcinoma ( 132 , 133 , 134 , 135 ).…”
Section: Role Of Platelets and Antiplatelet Therapy In Cancer And Atherosclerotic Heart Diseasementioning
confidence: 99%